Patient satisfaction after total knee arthroplasty: A retrospective observational study. - Kumar, Thatipamula Praful; Dr. D. Sneha (Student’s Journal of Health Research Africa, 2025)
Background: Patient satisfaction is a key measure of total knee arthroplasty (TKA) success. Despite advances, up to 19% remain dissatisfied. This study assessed satisfaction, functional improvement, and influencing factors in an Indian cohort using the Oxford Knee Score (OKS) and Kellgren–Lawrence (KL) grading. Methods: A retro-prospective observational study was conducted on 243 patients (301 knees) undergoing unilateral or bilateral primary TKA between September 2014 and November 2016 at a tertiary care hospital. Demographic data, comorbidities, diagnosis, and postoperative complications were recorded. Functional outcomes were assessed using pre- and postoperative OKS at ≥12 months follow-up. Satisfaction rates were documented using direct patient responses. Statistical analysis included chi-square and t-tests, with significance set at p < 0.05. Results: Of 243 patients, 74.9% were female, and the mean age was 63.5 ± 7.50 years. Overall, 85.6% reported satisfaction with surgery. Satisfaction rates did not significantly differ by gender (p = 0.928) or age group (p = 0.216). Comorbidities influenced satisfaction: diabetes (76.3% vs. 88.6%, p = 0.033) and hypertension (80.7% vs. 91.7%, p = 0.026) were associated with lower satisfaction. In KL grade III knees, mean preoperative OKS improved from 18.5 ± 1.78 to 35.6 ± 4.44, and in KL grade IV knees, from 14.5 ± 2.44 to 33.1 ± 6.07 (p < 0.001 for both). Satisfied KL grade IV knees showed a greater mean improvement in OKS (21.2 ± 2.75) compared to grade III (18.1 ± 2.22, p < 0.001), despite poorer baseline scores. Conclusion: High satisfaction rates were observed after TKA, with significant functional improvement across KL grades. Diabetes, hypertension, and lower preoperative OKS were associated with reduced satisfaction. Functional gain was greater in advanced KL grade osteoarthritis. Recommendations: Comorbidity optimization, patient education, and tailored postoperative rehabilitation should be prioritized to enhance satisfaction and functional outcomes after TKA.